2012
DOI: 10.1111/j.1369-1600.2012.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired sleep quality and sleep duration in smokers—results from the German Multicenter Study on Nicotine Dependence

Abstract: Cigarette smoking is a severe health burden being related to a number of chronic diseases. Frequently, smokers report about sleep problems. Sleep disturbance, in turn, has been demonstrated to be involved in the pathophysiology of several disorders related to smoking and may be relevant for the pathophysiology of nicotine dependence. Therefore, determining the frequency of sleep disturbance in otherwise healthy smokers and its association with degree of nicotine dependence is highly relevant. In a population-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
102
4
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 46 publications
(75 reference statements)
12
102
4
7
Order By: Relevance
“…Consistent with our results, several investigators have reported that current smokers were more likely to have symptoms of insomnia, including shorter sleep time, longer sleep latency, higher rapid eye movement, sleep density, more episodes of sleep apnea, and more leg movements during sleep. [24][25][26][27] Sabanayagam and Shankar found that current cigarette smokers were nearly twice as likely to report insufficient sleep and rest as compared to non-smokers. 28 Prior research has suggested that nicotine has adverse pathophysiological effects on the brain and the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, several investigators have reported that current smokers were more likely to have symptoms of insomnia, including shorter sleep time, longer sleep latency, higher rapid eye movement, sleep density, more episodes of sleep apnea, and more leg movements during sleep. [24][25][26][27] Sabanayagam and Shankar found that current cigarette smokers were nearly twice as likely to report insufficient sleep and rest as compared to non-smokers. 28 Prior research has suggested that nicotine has adverse pathophysiological effects on the brain and the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Old person smokes influenced by psychological factors in smoking. That is, the psychological state of a person determines the length of a person smokes (Triyanti 2006;Cohrs, S., Rodenbeck, A., Riemann, D., Szagun, B., Jaehne, A., Brinkmeyer, J., & Dahmen, N. 2014). …”
Section: Smoking Behaviormentioning
confidence: 99%
“…A dose-response relationship was observed between the amount smoked and sleep symptoms. In multivariate analyses, no INTRODUCTION Many studies have investigated the relationship between smoking and sleep disorders (Cohrs et al, 2012;Javaheri, Shukla, & Wexler, 2012;Kim et al, 2012;Sabanayagam & Shankar, 2011); however, previous studies have rarely tested for gender differences in this association in the U.S. population. Tobacco smoking and male gender are among the well-established risk factors for sleep disordered breathing (SDB) (Punjabi, 2008).…”
Section: Smoking and Gender Are Known Risk Factors For Sleep Disordersmentioning
confidence: 99%